System Design of Mobile Augmented Book - Saraubon, Kobkiat; Nilsook, Prachyanun; Wannapiroon, Panita (International Journal of Interactive Mobile Technologies (iJIM), 2016)
Mobile technologies play an increasingly important role in education. Devices such as smart phones and tablets are becoming powerful tools in the hands for e-Learning, m-Learning and ubiquitous learning. In this paper, the authors propose analysis and design software architecture of a mobile augmented book for in-class and out-class learning. The aim is to improve the quality and usefulness of mobile learning by utilizing a physical book and a mobile device. Requirements, roles, and system architecture are discussed in terms of adaptive learning. The system architecture is based on a three-tier model; presentation tier, application logic tier and data tier. The application logic tier is comprised of four main components including 1) Profile/Registration, 2) Content/ Administration, 3) Communication 4) Quiz and 5) Report. The data tier consists of 1) Cloud Service, 2) Media Server and 3) Database. The presentation tier is designed to support all mobile devices--smart phones and tablets and all popular platforms including Android, iOS, Windows phone, Tizen, Ubuntu, Firefox and BlackBerry. JSON and Streaming media are used for the communications between the presentation tier (client devices) and the application logic tier. The data tier consists of 1) repository using cloud service and media server for storing and retrieving digital contents and 2) database for credentials, content descriptions and meta-data.